Suggesting a method for managing expected health and safety risks from the design phase of construction projects - wassouf, hanan (Latakia University Journal -Engineering Sciences Series, 2025)
The construction sector is characterized by its dynamic nature, long working hours, and heavy reliance on manual labor. Despite the fact that safety procedure costs are significantly lower than the costs of accidents and injuries, the construction industry consistently ranks among the top industries with the highest rates of workplace injuries and fatalities. Safety planning is critical in construction; however, safety management on construction sites is typically limited to measures implemented during the execution phase, separate from project design and planning stages. This necessitates the adoption of a proactive safety management strategy instead of traditional methods. Research has demonstrated that making sound decisions during the design phase significantly enhances safety levels on construction sites. This study introduces a methodology for proactive safety management aimed at early hazard control and the reduction of injuries and fatalities. It involves calculating the risk levels associated with construction elements based on twelve major hazards present in projects. By determining the overall risk value during the design phase, the methodology enables effective control of project risks and design modifications to achieve the lowest possible risk level for each project day. Furthermore, it identifies optimal mitigation measures for high-risk factors and incorporates proactive design strategies in early stages to minimize risks.